Network-Coding-Based Energy-Efficient Data Fusion and Transmission for Wireless Sensor Networks with Heterogeneous Receivers - Lei Wang; Yuwang Yang; Wei Zhao; Lei Xu; Shaohua Lan (International Journal of Distributed Sensor Networks)
This paper proposes a multirate network coding scheme to improve the energy efficiency of wireless sensor networks (WSNs). Firstly, a five-layer network model is introduced, in which a perfect solution can always be achieved. Then, a network topology which belongs to the five-layer network model will be established from the given sensor networks so that the receivers can receive data at a higher rate without introducing excessive additional transmissions, which improves the energy efficiency as a result. The performance of the proposed scheme is evaluated in a simulated instance, and the result shows that 9% of transmission overhead can be saved compared with traditional scheme.